Retrospective Study: Management of Atopic Dermatitis - Adji, Aryani; Cahyadi, Alexandro Ivan (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Atopic dermatitis (AD) is a chronic skin inflammatory disease characterized by mild to severe itching, relapses, and mostly appears in infants and children. Although there have been current advances in the management of AD, satisfactory treatment has not been achieved. Purpose: To evaluate the treatment of patients with AD in order to provide better management. Methods: A retrospective study of newly diagnosed AD patients at the Allergy and Immunology Division of the Outpatient Unit, Dermatology and Venereology Clinic, Prof. Dr. R.D. Kandou Hospital Manado from 2019-2021. Result: Antihistamines were the most widely prescribed medication, administered to 108 patients of all patients' visits, and 94 (87%) of them were given cetirizine (the most widely prescribed type). Emollients were used adequately; they included petroleum jelly in 82 patients (90.1%) and urea 10% cream in 9 patients (9.9%). Conclusion: There were 108 AD patients in Dermatology and Venereology Clinic, Prof. Dr. R.D. Kandou Hospital Manado from 2019-2021. Treatment with antihistamine and emollient therapy gave satisfactory results.